Faktor risiko dan asupan isoflavon pada pasien kanker payudara - I Wayan Dwija Karyasa; Johan Kurnianda; Herni Astuti (Jurnal Gizi Klinik Indonesia, 2014)
Background: Breast cancer is noncommunicable chronic disease the prevalence of which is increasing all over the world, including in Indonesia and particularly East Java. Causes of breast cancer are unknown. Some studies show risk factors for breast cancer are hormonal, genetic, reproductive and endocrinologic factors. There is the isoflavon compound in soybeans that is known as anti-cancer with anti-estrogen activities.Objective: The study was aimed at identifying risk factor and the difference of isoflavone intake between breast cancer patients and healthy people in hospitals.Method: The study was analytic observational using matched case-control study design at comparison 1:2 with matching on a status of menopause. Cases were positive receptor estrogen breast cancer patients newly diagnosed during the first visit at hospital outpatient Oncologic Surgery Polyclinic. Controls were staff considered healthy based on the result of health examination at Dr. Ramelan Naval Hospital of Surabaya. Cases comprised 49 people and control 98 people taken through consecutive method. Data consisted of an identity of samples, weight, height, isoflavone intake, family history, use of hormone replacement therapy and parity. Intake of isoflavones was obtained from semiquantitative food frequency questionnaire (SQ-FFQ) and statistical test used Chi-Square and Odd Ratio (OR).Results: There was the difference in isoflavone intake and family history between cases and controls (p<0.05) and there was an association between isoflavone intake (OR=2.58; p=0.007) and family history (OR=18; p=0.002) and the incidence of breast cancer. There was no association between the status of obesity, parity, and use of hormone replacement therapy.Conclusion: There are differences in isoflavone intake of breast cancer patients compared with healthy people and there was no difference in the status of obese breast cancer patients compared to healthy individuals and isoflavone intake less 2.85 times the risk of breast cancer compared with adequate intake of isoflavones.